Pattern and Factors Associated with Medication Adherence to Antihypertensive Medications Among Stroke Survivors - Ogunjimi, LO; Toyale, RA; Oyenuga, IO; Oyebisi, OO; Motolase, OR; Osalusi, BS (Annals of Health Research (Onabanjo University Teaching Hospital), 2024)
Background: Hypertension is a major risk factor for initial and recurring strokes. Objective: To determine medication adherence and blood pressure control among stroke survivors. Methods: This one-year cross-sectional study recruited 95 consenting neuroimage-confirmed stroke patients attending the neurology clinic with confirmed hypertension. Stroke severity, functional outcome, and medication adherence were evaluated using the National Institute of Health Stroke Score (NIHSS), the Modified Rankin Scale (MRS), and the Morinsky Medication Adherence Scale (MMAS-8), respectively. Results: There was a preponderance of male participants [49 (89.1) vs 6 (10.1); p = 0.887], older participants [61.01±11.58 years vs 51.20±8.28 years; p = 0.010] and diabetes mellitus patients [26 (30.6%) vs 0 (0.0%) p = 0.040] among ischaemic cohort compared to the haemorrhagic cohort. Based on the grade of medication adherence, there was a higher mean Diastolic Blood Pressure (DBP) [81.99±10.89 mmHg vs 91.91±17.25 mmHg vs 84.0±18.166 p = 0.043], and Systolic Blood Pressure (SBP) [129.41±16.74 vs 143.55±25.97 vs 145.60±40.08; p = 0.025] among participants with low adherence. Factors associated with medication adherence in stroke survivors were SBP at one year (p = 0.025), DBP at one year (p = 0.043), and the number of antihypertensive medications taken (p = 0.010). SBP at one year was the only independent predictor of medication adherence. Conclusion: High medication adherence was associated with improved BP control among stroke survivors. As such, policy and clinical focus should be geared towards ensuring medication adherence in stroke survivors.